Visual strategy : strategy mapping for public and nonprofit organizations - Bryson, John M. (John Moore), 1947-; Eden, Colin; Ackermann, Fran. (USA : Jossey-Bass, 2014)
"Strategic planning becomes visual with strategy maps and the tools, techniques, and guidance for turning them into effective action.Developed as a companion workbook to John Bryson's best-selling Strategic Planning in Public and Nonprofit Organizations, Visual Strategy: A Workbook for Strategy Mapping in Public and Nonprofit Organizations, goes beyond making the case for good and effective strategic planning to making strategy visual through effective strategy mapping. Strategy mapping prevents groups of people from talking over one another and going around in circles. It helps people speak and be heard, produce lots of ideas and understand how they fit together, make use of causal reasoning, and clarify ultimately what they want to do in terms of mission, goals, strategies, and actions. Strategy mapping can join process and content in such a way that good ideas worth implementing are found and the agreements and comments needed to implement them are reached. The result is living strategic plans that act as useful guides to action.With detailed examples, actual strategy maps, process guidelines and hand-drawn illustrations, the book will help leaders, managers, students and other professionals see patterns across mission, goals, strategies and actions while helping to identify areas of alignment and misalignment and determine, real time, where elements are needed, missing or not useful in a strategic plan.For leaders and managers of public and nonprofit organizations, facilitators and consultants, professors and students of strategic planning, strategic management, strategic mapping, and public policy, professional development workshops focused on strategic planning and strategy mapping"--
Includes bibliographical references.
Keywords: Strategic planning; Public administration -- Management; Nonprofit organizations; BUSINESS & ECONOMICS / Strategic Planning